Аналіз можливої газопроникності сталевих труб газопроводів під час рекуперативного підігрівання природного газу - Кришкін, Б. Б.; Kryshkin, Boris (КНТУ, 2014)
У статті описано методику оцінки ймовірності підсмоктування водяної пари з внутрішнього простору рекуперативних теплообмінних апаратів, які можуть використовуватися для підігрівання природного газу на теплових електростанціях. In the article the method of determination of possibility of seepage of aquatic steams is described from internal space of rekuperativе heat-exchange vehicles which can be used for heating of natural gas on thermal power-stations. It is rotined that at the existent modes of heating of natural gas the danger of penetration of water steams through the layer of metallic seamless pipe absents practically. The method of estimation can be used for planning of tubular recuperators.
The analysis of possible steel tubes gas heat vapour emissivity during of natural gas recuperative heating
Keywords: тепло; рекуператор; труба; газопроникність; дифузія; швидкість; температура; warm; recuperator; pipe; gas-penetrability; diffusion; speed; temperature